Rinozigomicosis y zigomicosis subcutánea en equinos, 2.Tratamiento con yoduro de potasio o acetonida de triamcinolona - Torres G., Jorge E.; Jaramillo S., César A. (Instituto Colombiano Agropecuario, 2019)
In the department of Caqueta, Colombia, 31 horses affected of rhinozigomycosis (nasal granuloma) and 13 affected of zigomycosis were selected in order to evaluate the curative effect of potassium iodide (1K) and of acetonide of triamcinolone (VetalogR. In a first group, consisting of 18 animals affected of rhinozigomycosis and 4 of dermal zigomycosis, curative responses were found on 5 and 2 animals respectively, when 1K was applied intravenously (55-490 g distributed between 11 to 28 dosages). Group two, that consisted of 15 animals affected of rhinozigomycosis (include 3 non-responsive of group one) and 6 affected of dermal zigomycosis, were treated with acetonide of triamcinolone (30-150 mg, dividend on 1-3 dosages at 3 to 10 days interval, IM). Curative responses were observed on 13 and 3 animals respectively. 1K was able to produce healing of dermal and nasal cases but the success rate was low. Due to the long term treatment under field conditions there were 9 yugular extravasation causing interruption of treatments and/or death of animals. Although acetonide of triamcinolone showed a high number of curative responses at the beginning, 7 cases of rhinozigomycosis showed recurrence at 120 to 490 days after treatment. These recurrences were mainly observed on animals receiving low dosages. Triamcinolone should be used with caution, avoiding its application on pregnant or milking mares or in old or weak animals.